For the Purpose of Accountability: The Need for a Comprehensive Recordkeeping Act - Valpy, D. Richard (Archivaria, 2019)
The adoption of digital technologies has been sudden, pervasive, and global in scope. A consequence of this paradigm shift is the threat these technologies pose to the effective accountability of our public institutions. Given the fundamental importance of accountability to democracy, and the central role records play in documenting accountability, records management cannot be discretionary. It must be a matter of law. The requirements of an effective records management system mirror those of the financial management systems used by governments across Canada. Modern financial management systems are comprehensive regimes, which have developed over decades. They incorporate legislation, policy, procedures, standards, and the means to verify compliance. To create a similar regime for the management of records as sources of evidence, governments need to establish strong, enforceable legislation and policies, and the creators, managers, and users of information need to apply standards-based approaches to all aspects of the care of information and evidence. RÉSUMÉ L’adoption des technologies numériques a été soudaine, envahissante et globale. Une conséquence de ce changement de paradigme est la menace que font peser ces technologies sur la responsabilisation réelle de nos institutions publiques. Étant donné l’importance cruciale de la responsabilisation pour la démocratie et le rôle central des documents dans la documentation de la responsabilisation, la gestion des documents ne peut être laissée à la discrétion de chacun. Elle doit faire l’objet d’une loi. Les exigences pour un système de gestion des documents efficace reflètent celles des systèmes de gestion financière utilisés par les gouvernements partout au Canada. Les systèmes de gestion financière modernes sont des régimes complets qui ont été développés sur des décennies. Ils comprennent des lois, des politiques, des procédures, des normes et des moyens de contrôler la conformité. Pour créer un régime similaire pour la gestion des documents comme sources de preuve, les gouvernements doivent établir des lois et des politiques fortes et exécutoires et les créateurs, gestionnaires et utilisateurs de l’information doivent appliquer à tous les aspects de la prise en charge de l’information et des preuves des approches basées sur des normes.